Bantaeng Geographical Indication Arabica Coffee Coffea Arabica: Does Altitude Affect the Quality of the Coffee Bean? - Andi Ilham Latunra; Tri Diah Pasinta; Muhammad Ruslan Umar; Ardiansyah (Postgraduate, University of Mataram, 2023)
Indonesia has a wide variety of coffee varieties, and is the 4th largest coffee exporter in the world. This study aims to discover about the difference of coffee bean quality from different altitude. In this study Coffee samples Coffea arabica L. which will be used is taken from Bantaeng Regency, South Sulawesi. The selected sample is coffee beans that are red and have matured at every altitude where they grow. Station I is between 800-1000 masl, station II is between 1000-1200 masl and station III is between 1200-1400 masl. The quality test including Physical test, Bean weight, volume, and smell test (rotten aroma) as in SNI 01-2907-2008. The result shows that the quality from each station is different. Thus this research conclude that the altitude will affect the bean quality of Coffea arabica from Bantaeng Geographical Indication area.